Development of Quantum Learning-Based Articulate Storyline Learning Media to Improve Students' Mathematical Communication Skills - Mizta Dwi Hafizah Furqoni; Waminton Rajagukguk; Yulita Molliq Rangkuti (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2023)
The main purpose of this study is to describe the validity, practicality, and effectiveness of articulate storyline learning media based on quantum learning. This medium is specifically designed to improve students' mathematical communication skills. The research conducted is included in the development research category, with the ADDIE model as the chosen development model. The results showed that the learning media met the required validity criteria, which was shown from the analysis conducted by validators. In addition, the learning media proved to be practical, as observed during its implementation, and was considered effective in improving students' mathematical communication skills. This effectiveness is evidenced by the achievement of students' communication skills classically, and students are interested in learning media. In addition, the average N-Gain is in the medium category which indicates that the learning media is successful in improving students' mathematical communication skills.Keywords: Learning Media, Articulate Storyline, Quantum Learning, Mathematical Communication Skills